Applied strategic planning : a comprehensive guide - Goodstein, Leonard (McGraw Hill New YorkUS, 1993)
Presents the appplied strategic planning model and provides step-by-step methodology and technology for conducting the strategic planning process. Targets senior managers and consultants, especially. Deals with topics including: culture and applied strategic planning; values scan; contingency planning; and implementation.